Consequences of contaminant mixture on the dynamics and functional diversity of bacterioplankton in a southwestern Mediterranean coastal ecosystem. (February 2016) - Pringault, Olivier; Lafabrie, Céline; Avezac, Murielle; Bancon-Montigny, Chrystelle; Carre, Claire; Chalghaf, Mohamed; Delpoux, Sophie; Duvivier, Adrien; Elbaz-Poulichet, Françoise; Gonzalez, Catherine; Got, Patrice; Leboulanger, Christophe; et al.
Abstract: Contamination of coastal environments is often due to a complex mixture of pollutants, sometimes in trace levels, that may have significant effects on diversity and function of organisms. The aim of this study was to evaluate the short-term dynamics of bacterioplankton exposed to natural and artificial mixtures of contaminants. Bacterial communities from a southwestern Mediterranean ecosystem, lagoon and the bay (offshore) of Bizerte were exposed to i) elutriate from resuspension of contaminated sediment, and ii) an artificial mixture of metals and herbicides mimicking the contamination observed during sediment resuspension. Elutriate incubation as well as artificial spiking induced strong enrichments in nutrients (up to 18 times), metals (up to six times) and herbicides (up to 20 times) relative to the in situ concentrations in the offshore station, whereas the increases in contaminants were less marked in the lagoon station. In the offshore waters, the artificial mixture of pollutants provoked a strong inhibition of bacterial abundance, production and respiration and significant modifications of the potential functional diversity of bacterioplankton with a strong decrease of the carbohydrate utilization. In contrast, incubation with elutriate resulted in a stimulation of bacterial activities and abundances, suggesting that the toxic effects of pollutants were modified by the increase in nutrient and DOM concentrations due to the sediment resuspension. The effects of elutriate and the artificial mixture of pollutants on bacterial dynamics and the functional diversity were less marked in the lagoon waters, than in offshore waters, suggesting a relative tolerance of lagoon bacteria against contaminants. Graphical abstract: Highlights: Bacterioplankton was exposed to pollutant mixture created from sediment resuspension. Strong enrichment in metals, herbicides, DOC and nutrients were observed. Bacterial abundance and activities were inhibited by metals and herbicides. Nutrients and DOC modified the inhibitory effects of metals and herbicides. Inhibitory effects were more marked in offshore waters than in lagoon waters.